1997
DOI: 10.1159/000291848
|View full text |Cite
|
Sign up to set email alerts
|

Stress of Female Infertility: Relations to Length of Treatment

Abstract: The psychology of infertile women was investigated with a battery of psychological tests consisting of a semistructured interview, State Trait Anxiety Inventory (STAI), Center for Epidemiologic Studies Depression Scale (CES-D), and Cornell Medical Index (CMI). The subjects were 107 infertile women being treated for infertility. The semistructured interviews revealed that the stress factor for infertile women changes with the length of infertility. In the early states, the main stress is related to a physical i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0
6

Year Published

2003
2003
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(26 citation statements)
references
References 2 publications
1
19
0
6
Order By: Relevance
“…In their study, they compared two groups suffering from infertility for <4 years and >4years and reported depression more frequently in the latter group. 19 However, a study by Guz H. showed that age and duration of infertility were inversely correlated with depression. According to them, the patients are able to accept the problem as they grow older and the longer infertility persists.…”
Section: Discussionmentioning
confidence: 99%
“…In their study, they compared two groups suffering from infertility for <4 years and >4years and reported depression more frequently in the latter group. 19 However, a study by Guz H. showed that age and duration of infertility were inversely correlated with depression. According to them, the patients are able to accept the problem as they grow older and the longer infertility persists.…”
Section: Discussionmentioning
confidence: 99%
“…Although we could not find the effect of infertility duration on the anxiety scores, unusual persistence with which women cling desperately to treatment despite the length tend to bring about ''chronic feelings of unhappiness''. Chiba and co-workers suggested that the psychological symptoms of infertile women seem to be close to the level of neurosis, and long-term infertility might aggravate their neurotic tendency rather than anxiety itself (15).…”
Section: Discussionmentioning
confidence: 99%
“…Based on the analysis of psychological tests, Chiba et al . found that stress affects a woman's duration of infertility [15]. Akizuki et al .…”
Section: Introductionmentioning
confidence: 99%